Asuhan Keperawatan Jiwa Pada Pasien Dengan Resiko Perilaku Kekerasan Di Wisma Nuri Rsj Prof Hb Saanin Padang - Indah Lediana; Vivi Yuderna; Ramaita .; Dwi Happy Anggia Sari (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
The risk of violent behavior is one of the psychiatric nursing problems in patients with severe mental disorders caused by the inability to control emotions, which may potentially harm oneself, others, or the surrounding environment. Data from the World Health Organization (WHO) in 2024 showed that mental disorders have increased, affecting more than 1.1 billion people worldwide. Based on medical record data at Prof. HB. Saanin Mental Hospital Padang, cases of violent behavior were reported as many as 213 cases in 2023, 138 cases in 2024, and 159 cases in 2025.This study aimed to provide mental health nursing care for patients with a risk of violent behavior. The method used in this scientific paper was a case study approach with the nursing process, which includes assessment, diagnosis, planning, implementation, and evaluation. The implementation of nursing care was carried out from February 9 to 14, 2026, with five meetings. Nursing interventions were provided through deep breathing exercises, hitting a pillow as a safe outlet for anger, medication adherence education, effective verbal communication, and spiritual activities. The results showed that the patient became calmer, more cooperative, able to control anger, did not use harsh language, and adhered to medication. In conclusion, mental health nursing care can reduce the signs and symptoms of the risk of violent behavior. It is expected that nurses and families play an active role in preventing relapse.